Characterization of Poultry Production Systems and associated physical egg quality characteristics in Tigania west Meru County - Thuita , John (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Characterization of Poultry Production Systems and associated physical egg quality characteristics in Tigania west Meru County Nancy Nganga Ikiara, Martin Mbare, Timothy Mutwiri Kithinji and John Thuita Poultry farming is a significant component of modern-day agriculture and contributes to overall food security through production of eggs and white meat. Furthermore, although the livestock subsector contributes 18% of global greenhouse gas emissions, poultry production leaves a comparatively smaller carbon footprint per unit of product compared to ruminant production. Contrary to the prevailing situation in Meru County, therefore, poultry production needs to play a bigger role in efforts to enhance food security. The purpose of this research was to characterize poultry production in Tigania West sub- County, with respect to adoption levels, farmer demographics, land sizes and physical egg quality parameters associated with different production systems. A total of 83 farmers were interviewed using a structured questionnaire. The questionnaire response rate was 94% (78/83). Among the respondents, 53/78 (67.9%) had poultry in their farms. Out of the 53 poultry farmers, 81.1% (43/53) were practicing the free-range production system, 17% (9/53) semi-intensive production system and only 2% (1/53) were practicing the intensive production system. Not surprisingly therefore, local breeds and improved Kienyeji chicken were the most common breeds kept in the small holder farms, a majority (95%) of which were less than 5 acres in size. Physical egg defects included broken shells which were observed in 7.5% and 9.3% of eggs in the free-range and semi-intensive production systems, respectively. The most prevalent egg shell defect was soiling, which was detected in 80.7% (75/93) of the eggs collected from the free-range production system. Eggs collected from the intensive and semi-intensive systems were not soiled. Eggs shape index was 76.5, 73.4 and 72.1% for the intensive, semi-intensive and free-range production systems respectively. The Tigania west poultry sector is therefore characterized by high adoption levels, particularly of the low risk, low input and eventually low returns free-range production system. Key words: Poultry, production system, physical egg characteristics, shell defects, Tigania west.